2000
DOI: 10.1093/emboj/19.10.2292
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repression by Pax5 (BSAP) through interaction with corepressors of the Groucho family

Abstract: Pax5 (BSAP) functions as both a transcriptional activator and repressor during midbrain patterning, B-cell development and lymphomagenesis. Here we demonstrate that Pax5 exerts its repression function by recruiting members of the Groucho corepressor family. In a yeast two-hybrid screen, the grouchorelated gene product Grg4 was identi®ed as a Pax5 partner protein. Both proteins interact cooperatively via two separate domains: the N-terminal Q and central SP regions of Grg4, and the octapeptide motif and C-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
204
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(213 citation statements)
references
References 48 publications
8
204
0
1
Order By: Relevance
“…Members of the other subgroup, e.g., Grg5 in mice and AES in humans, contain the amino-terminal region of gro, including the Q-rich domain, but lack most of the variable region and the entire WD-40 repeat region. Mammalian gro homologues in the first group bind to transcription factors that target gene repression (Aronson et al, 1997;Roose et al, 1998;Eberhard et al, 2000;Tetsuka et al, 2000;Wang et al, 2000;Brantjes et al, 2001), whereas the short form of gro, such as XGrg5 in Xenopus, has been shown to enhance transcriptional activity (Roose et al, 1998;Brantjes et al, 2001). It has been speculated that Grg5 may act as a dominant negative molecule within a transcription complex.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the other subgroup, e.g., Grg5 in mice and AES in humans, contain the amino-terminal region of gro, including the Q-rich domain, but lack most of the variable region and the entire WD-40 repeat region. Mammalian gro homologues in the first group bind to transcription factors that target gene repression (Aronson et al, 1997;Roose et al, 1998;Eberhard et al, 2000;Tetsuka et al, 2000;Wang et al, 2000;Brantjes et al, 2001), whereas the short form of gro, such as XGrg5 in Xenopus, has been shown to enhance transcriptional activity (Roose et al, 1998;Brantjes et al, 2001). It has been speculated that Grg5 may act as a dominant negative molecule within a transcription complex.…”
Section: Introductionmentioning
confidence: 99%
“…All members of the Bar-homeodomain family have one or more N-terminal engrailed homology-1 (eh-1) motifs, which are generally recognized as recruitment points for TLE͞Groucho-related factors. Mammalian homologs of Drosophila Groucho have been repeatedly identified as important corepressors for homeodomain proteins and other transcription factors (13)(14)(15)(16)(17)(18). In the skin, TLE͞Groucho factors acting through Tcf3 have been implicated in suppressing the terminal differentiation of epidermis (19).…”
mentioning
confidence: 99%
“…But until now, the precise molecular mechanisms of Pax2 in the mullerian duct development remain obscure. Early studies showed that the Pax2 protein could interact with some repressor proteins to change the positive regulators to negative during the period of transcription [28]. In recent works, scholars identified that the Pax2 transactivation domain is phosphorylated by the c-Jun N-terminal kinase (JNK) [29].…”
Section: Discussionmentioning
confidence: 99%